Efektivitas Kaderisasi Da’i melalui Program Dawrah Taḥfiẓ Al-Qur’an - Milah Milatul Mustaqimah; Rodliyah Khuza’I (Jurnal Riset Komunikasi Penyiaran Islam, 2021)
Abstract. This study aims to determine the implementation of the Dawrah Taḥfiẓ Al-Qur'an program, evaluation of the Dawrah Taḥfiẓ Al-Qur'an program, and the effectiveness of the regeneration of preachers through the Dawrah Tafi Al-Qur'an program at PPI 67 Benda city of Tasikmalaya. This type of research is a qualitative research, the method used is the method of documentation and interviews. The population and samples of this research are: students, muhaffizah, and coordinator of muhaffizah 67 Benda city of Tasikmalaya. The results of this study are: the implementation of the Dawrah Taḥfiẓ Al-Qur'an program PPI 67 Benda in the city of Tasikmalaya, which is carried out internally by the pesantren, carried out in collaboration with the Taḥfiẓ Miftahul Khoir Islamic boarding school, Bandung district. The results of the evaluation of the Dawrah Taḥfiẓ Al-Qur'an program at PPI 67 Benda in the city of Tasikmalaya, found internal problems for students. The effectiveness of the regeneration of preachers through the Dawrah Tafi Al-Qur'an program of PPI 67 Benda of the city of Tasikmalaya in this study found that, the implementation of the Dawrah Tafi Al-Qur'an program organized by PPI 67 Benda of the City of Tasikmalaya was quite effective, because there were still obstacles that found in the program, namely from internal students who participated in the Dawrah Taḥfiẓ Al-Qur'an program. Abstrak. Penelitian ini bertujuan untuk mengetahui pelaksanaan program Dawrah Taḥfiẓ Al-Qur’an, evaluasi program Dawrah Taḥfiẓ Al-Qur’an, serta efektivitas kaderisasi Da’i melalui program Dawrah Taḥfiẓ Al-Qur’an PPI 67 Benda kota Tasikmalaya. Jenis penelitian ini adalah penelitian kualitatif, metode yang digunakan yaitu metode dokumentasi dan wawancara. Adapun populasi dan sampel penelitian ini yaitu: santri, muhaffizah, dan koordinator muhaffizah 67 Benda kota Tasikmalaya. Adapun hasil penelitian ini yaitu: pelaksanaan program Dawrah Taḥfiẓ Al-Qur’an PPI 67 Benda kota Tasikmalaya, yaitu dilaksanakan secara internal pesantren, dilaksanakan dengan kerjasama pesantren Taḥfiẓ Miftahul Khoir kabupaten Bandung. Hasil evaluasi program Dawrah Taḥfiẓ Al-Qur’an PPI 67 Benda kota Tasikmalaya, menemukan adanya kendala dalam internal santri. Efektivitas kaderisasi Da’i melalui program Dawrah Taḥfiẓ Al-Qur’an PPI 67 Benda kota Tasikmalaya dalam penelitian ini menemukan bahwa, pelaksanaan program Dawrah Taḥfiẓ Al-Qur’an yang diselenggarakan oleh PPI 67 Benda Kota Tasikmalaya cukup efektif, dikerenakan masih adanya kendala yang ditemukan dalam program tersebut yaitu dari internal santri yang mengikuti program Dawrah Taḥfiẓ Al-Qur’an.